PENERAPAN PRINSIP WISATA BAHARI DI DAYA TARIK WISATA PANTAI BAJULMATI - Amalia Dinda Candra Dewi; Garsione Agni Andrea (Jurnal Pariwisata Tawangmangu, 2026)
Bajulmati Beach in Malang Regency has significant potential as a marine tourism attraction, supported by sea turtle conservation efforts through the presence of Bajulmati Sea Turtle Conservation (BSTC). An analysis of the implementation of marine tourism principles indicates that the attraction at Bajulmati Beach also has the potential to serve as a tourism destination with educational and recreational value. This study aims to analyze the application of marine tourism principles at Bajulmati Beach, Malang Regency. This research employs a qualitative approach, with data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of marine tourism principles in the Bajulmati Beach tourism area has been effective, as reflected in three main areas: education, natural resource conservation, and the application of codes of conduct. The educational aspect is implemented through the “Sekolah Alam” (Nature School) program, informational media, and the involvement of tourists in conservation activities. The natural resource conservation aspect is demonstrated through sea turtle habitat management, coastal vegetation planting, and spatial planning of the area. Meanwhile, the code of conduct is applied to managers, tourists, and local communities through rules that support environmental sustainability. Thus, sea turtle conservation activities in the Bajulmati Beach area not only serve to preserve sea turtles but also support the development of sustainable marine tourism.